Effectiveness of Medicinal Plants for Glycaemic Control in Type 2 Diabetes: An Overview of Meta-Analyses of Clinical Trials - Merlin L. Willcox (Frontiers Media S.A., 2021)
Aims: To rank the effectiveness of medicinal plants for glycaemic control in Type 2 Diabetes (T2DM).Methods: MEDLINE, EMBASE, CINAHL and Cochrane Central were searched in October 2020. We included meta-analyses of randomised controlled clinical trials measuring the effectiveness of medicinal plants on HbA1c and/or Fasting Plasma Glucose (FPG) in patients with T2DM.Results: Twenty five meta-analyses reported the effects of 18 plant-based remedies. Aloe vera leaf gel, Psyllium fibre and Fenugreek seeds had the largest effects on HbA1c: mean difference –0.99% [95% CI−1.75, −0.23], −0.97% [95% CI −1.94, −0.01] and −0.85% [95% CI −1.49, −0.22] respectively. Four other remedies reduced HbA1c by at least 0.5%: Nigellasativa, Astragalus membranaceus, and the traditional Chinese formulae Jinqi Jiangtang and Gegen Qinlian. No serious adverse effects were reported. Several other herbal medicines significantly reduced FPG. Tea and tea extracts (Camellia sinensis) were ineffective. However, in some trials duration of follow-up was insufficient to measure the full effect on HbA1c (<8 weeks). Many herbal remedies had not been evaluated in a meta-analysis.Conclusion: Several medicinal plants appear to be as effective as conventional antidiabetic treatments for reducing HbA1c. Rigorous trials with at least 3 months’ follow-up are needed to ascertain the effects of promising plant-based preparations on diabetes.